Five-Year Review of the Foundations Onboarding Program for the UGA Cooperative Extension - Virginia Brown; Kristi Farner (Journal of Human Sciences and Extension)
This paper examines the successes and opportunities for improvement of a comprehensive professional development program at a state land-grant university. The Extension Committee on Organization and Policy (ECOP) recognizes turnover and retention as a systemic issue further compounded by heavy workloads and low salaries. According to the Motivation-Hygiene Theory, job satisfaction can increase when motivating factors, such as personal development opportunities, are implemented. Created over two decades ago, the University of Georgia’s Foundations program has been part of its onboarding process that provides agents and educators with the knowledge and skill development for success in their roles. Since 2016, it has largely targeted the same content for each new cohort of educators. While immediate post-evaluations have been conducted, no longitudinal effort existed to look at how well the program worked in preparing agents for their roles. A 5-year retrospective study was developed to examine the perceived success, as well as determine any potential areas that need knowledge and skill development. This article discusses both the agent’s and administrator’s perspectives on how well it prepared them for success. Additional trainings to address emergent issues are explored, and recommendations on how Extension can better prepare agents for success are made.